Comparison of biochemical analysis of fetal serum and fetal urine in the prediction of postnatal renal outcome in lower urinary tract obstruction. (27th April 2018) - Spaggiari, Emmanuel; Stirnemann, Julien J.; Benedetti, Sara; Dreux, Sophie; Salomon, Laurent J.; Blanc, Thomas; Rosenblatt, Jonathan; Favre, Romain; Ville, Yves; Muller, Françoise
Abstract: Objectives: To compare the prognostic value of fetal serum biochemistry and fetal urine biochemistry in predicting renal outcome in lower urinary tract obstruction (LUTO). Methods: We retrospectively studied renal outcome following a prenatal diagnosis of LUTO in cases for which both fetal blood and fetal urine were sampled. We classified the renal outcome as either "favorable, " when postnatal renal function was normal, or "adverse, " in the case of postnatal chronic renal failure or when renal histological lesions were present at autopsy in the case of termination of pregnancy. A prognostic model was constructed for urine and serum separately. β2‐Microglobulin was the only remaining independent predictor in fetal urine. β2‐Microglobulin in serum and urine were compared by using receiver operating characteristic curves. Results: In the 50 cases included, the rate of adverse outcome was 34 of 50(68%): autopsy confirmed severity of renal disease in all 27 cases who underwent termination of pregnancy, and among the 23 live born children, 7 developed renal failure. Fetal serum and urine markers were all significantly associated with renal outcome ( P  < .01). The receiver operating characteristic curves for fetal serum and fetal urinary β2‐microglobulin were similar (area under the curve = 0.908 versus 0.909, P  = .96). Conclusion: Fetal serum biochemistry and fetal urine biochemistry are of similar prognostic value in predicting postnatal renal outcome in fetuses with LUTO. Abstract : What's already known about this topic? Biochemical markers have been proposed to improve prenatal prognostic assessment of LUTO, focusing on serum and urine biomarkers. To date, there is no evidence that 1 or other of the 2 strategies is better. What does this study add? This study shows that fetal serum biochemistry and fetal urine biochemistry are of similar prognostic value in predicting postnatal renal outcome in fetuses with LUTO. The choice depends of the clinical context.